ETHNOMATHEMATICAL EXPLORATION OF THE APEM WONOLELO TRADITION IN SLEMAN REGENCY - Muhammad Mahlil Aliman Maba; Deny Hadi Siswanto; Nomalika Zindagi Caesaria (CV. Denasya Smart Publisher, 2025)
This study aims to explore and describe the mathematical concepts embedded in the Apem Wonolelo culture of Sleman Regency through an ethnomathematical approach. The research employed a qualitative method with an ethnographic design. Data were collected through participatory observation, in-depth interviews with apem makers and community leaders, as well as photographic and video documentation of the “Apeman” tradition. The data were analyzed qualitatively and descriptively through the stages of data reduction, data presentation, and conclusion drawing, with data validity ensured through source and technique triangulation. The results reveal five main aspects of ethnomathematics in the Apem Wonolelo tradition: (1) geometry and symmetry in the shape of the apem; (2) ratio and proportion in ingredient composition; (3) patterns and sequences in the production process; (4) measurement of volume and dough capacity; and (5) statistical concepts in the distribution tradition. Each of these aspects reflects the intuitive application of mathematical concepts in daily life. This study highlights that ethnomathematics not only represents local wisdom but also holds great potential as a contextual learning medium that connects culture, social values, and formal mathematical understanding in educational settings.